SAFETY AND EFFICACY OF HERBAL REMEDIES: A REVIEW OF THE MODELS FOR VALIDATION OF HERBAL REMEDIES OF SOME NEUROPHARMACOLOGICAL CONDITIONS. - OLAYIWOLA, Gbola (African Journal of Traditional, Complementary and Alternative Medicines, 2022)
Background: Herbal remedies are making waves in many neurological conditions, and it will be wrong to assume that they do not have to be subjected to the same rigorous ethical investigational pathways as for the synthetic medicines/remedies. The primary and most important concern of pharmacologists in the team of drug developers is the safety of the remedy, whether herbal or synthetic. The remedies are aimed at the human body for the alleviation of the medical condition, so it makes sense to protect that body against further injury. In this context, there is no consideration for a different treatment when herbs are involved. Methods: This review is based on the teaching approaches of the author, with a view to explaining the rationale for some of the experimental steps in neuropharmacological experiments, particularly with herbs. The issues of experimental models are discussed, with sufficient explanations for the choice of the model, the indices to monitor and the interpretation of the indices. Supporting literature are also provided as appropriate. Conclusions: Appropriate conclusions are drawn and the target audience are put in a good stead of the appreciation of why they do what they do, while correcting what they have not done well.